Geographical routing for WSN of street lighting monitoring and control system - Chunguo Jing; Liangchao Ren; Deying Gu (2010 International Conference On Computer Design and Applications, 2010)
In order to monitoring and control each street lighting, the wireless sensor network was developed and has been used in street lighting system. The system consists of the sensor node, the remote terminal unit (RTU) and the control center. The sensor nodes were installed at each lighting pole and make up a network with RTUs. In this paper, a geographical routing strategy was proposed based on the network features. According to the power substation powering scope, the lighting nodes was divided many clusters. In one cluster, the nodes and power substation distribution is either star or triangle. The node forwards the packet to the power substation where RTU installed in according to the distance to the RTU in star distribution. It uses cluster serial number to avoid the packet dissemination to neighbor cluster. The node serial number and packet time stamp were used to find out duplicate forwarded packet. The forwarding no convergence problem was solved by using agent node in triangle distribution. The proposed geographical routing for street lighting system is simple and not need to maintain net topology and complex path discovery algorithms.